The effects of oral medroxyprogesterone acetate combined with conjugated equine estrogens on inflammation in postmenopausal women: a systematic review and meta-analysis of randomized controlled trials - Qiu, Jiahui; He, Yunan; Li, Jinhong; Safargar, Mohammad; Prabahar, Kousalya; Shi, Qingquan (Frontiers in Endocrinology, 2025)
Background and AimMenopausal hormone therapy (MHT) remains a pivotal approach in managing menopausal symptoms; however, its effects on inflammation and cardiovascular risk markers are still under debate. In particular, the combination of medroxyprogesterone acetate (MPA) and conjugated equine estrogens (CEE) has shown variable impacts on inflammatory biomarkers. This systematic review and meta-analysis aimed to synthesize evidence from randomized controlled trials (RCTs) assessing the effects of oral MPA combined with CEE (MPA/CEE) on systemic inflammation in postmenopausal women.MethodsThirteen RCTs (comprising 16 arms) reporting data on inflammatory markers, including C-reactive protein (CRP), fibrinogen, homocysteine, and interleukin-6 (IL-6), were included, with a total sample size of 2,278 participants. A random-effects model was used to calculate pooled weighted mean differences (WMDs) with 95% confidence intervals. Subgroup and sensitivity analyses were performed to explore heterogeneity, and publication bias was assessed using Egger's test and trim-and-fill methods.ResultsMPA/CEE treatment was associated with a significant decrease in CRP levels (WMD = -0.173 mg/dL; 95% CI: -0.25 to -0.10; P < 0.001), particularly among postmenopausal women aged <60 years, trials with MPA doses ≤2.5 mg/day, and those with BMI <25 kg/m². In addition, a significant reduction in fibrinogen levels was observed (WMD = -60.588 mg/dL; 95% CI: -71.436 to -49.741; P < 0.001), especially at MPA doses ≤2.5 mg/day and in women with BMI <25 kg/m². No statistically significant changes were found in homocysteine or IL-6 levels.ConclusionWhile MPA/CEE therapy significantly reduces CRP and fibrinogen, key inflammatory and cardiovascular risk markers, these findings suggest a notable protective effect of oral MPA/CEE on inflammation, highlighting the need for individualized therapeutic strategies based on patient risk profiles.